2014
DOI: 10.1016/j.econedurev.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tuition fees on transition from high school to university in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 12 publications
2
36
1
Order By: Relevance
“…A study of the results from a natural experiment in Germany (upon introduction of tuition fees in seven out of 16 federal states in 2007) confirms there is considerable influence on changes in the number of students (Bruckmeier & Wigger, 2014;Huebner, 2012). An empirical approach to justify a hypothetical situation of the influence of countrywide tuition fees in German states shows an increase in the number of students of up to 6.85 percentage points.…”
Section: Existing Empirical Evidencementioning
confidence: 97%
“…A study of the results from a natural experiment in Germany (upon introduction of tuition fees in seven out of 16 federal states in 2007) confirms there is considerable influence on changes in the number of students (Bruckmeier & Wigger, 2014;Huebner, 2012). An empirical approach to justify a hypothetical situation of the influence of countrywide tuition fees in German states shows an increase in the number of students of up to 6.85 percentage points.…”
Section: Existing Empirical Evidencementioning
confidence: 97%
“…BAföG recipients were, generally, also obligated to pay the fees and their parents were expected to increase their nancial support accordingly if possible. Evidence on whether the introduction of the fees had an e ect is mixed (Hübner, 2012;Bruckmeier and Wigger, 2014). We construct an indicator based on the students' place of living in a certain year and merge information from federal amendments indicating which federal state introduced tuition fees in which year.…”
Section: Further Robustness Checksmentioning
confidence: 99%
“…Taking advantage of this setting, Hübner (2012) found a negative effect of tuition fees on enrolment, larger than in previous studies for European countries, but similar to those reported for the USA. Dietrich and Gerner (2012) found that the introduction of tuition fees reduced the propensity of high school graduates to enrol at a university and favoured the vocational training option, whereas Bruckmeier and Wigger (2014) found no evidence that the introduction of tuition fees had a general negative effect on enrolment.…”
Section: Tuition Fees As Education Policymentioning
confidence: 99%